(untitled) (Journal of Hama University, 2020)
The increasing desire of patients to obtain their prosthetics as soon as possible has led researchers to work on ways and materials that contribute to enhancement and acceleration of the healing of the alveolar after extraction, as well as prevent the occurrence of complications that delay the healing process . Aims of research: Evaluation the effect of local application of simvastatin after , posterior mandibular extraction, on soft tissue healing and protection from Dry Socket Materials and methods: The study included 60 cases of simple extraction of lower molars the sample was randomly divided into three equal groups: In the first group ,gelatin sponge soaked in simvastatin 10 mg was applied in the socket ,and only gelatin sponge was applied in the socket in the second study group. The third group was control group ( the socket was left to heal spontaneously). Patients were clinically monitored after 2,7,30 days to assess the degree of healing. Results: it seemed like the healing was faster and better in first group(gelatin sponge soaked in simvastatin 10 mg ) , no statistically significant differences between the three groups about incidence of dry socket.